Utilization Of UML (Unified Modeling Language) In The Design Of Academic Information Systems Based On The OOAD Method - Laqma Dica Fitrani; Ari Cahaya Puspitaningrum (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
Junior high school is one of the organizations whose business processes involve teaching and learning activities under the principal's responsibility. SMP ABC is a junior high school that continually strives to improve the quality of education, one of which is its academic services. However, the process of storing and processing data at SMP ABC still uses Microsoft word and Microsoft excel. Hence, the data management process is not good and allows a lot of errors in processing academic data. The academic information system is a system that can help solve the problem of errors in data processing and make the educational service process better and more effective. So SMP ABC also needs to implement an academic information system. The results of this study are to analyze and design educational information systems using the OOAD method using UML (Unified Modeling Language) tools with several diagrams, including use case diagrams, sequence diagrams, and ERD, to facilitate academic data management and improve efficiency and effectiveness so that management data on SPM ABC can be computerized appropriately.